Effectiveness of Dispositional Mindfulness on Mental Health Markers and Well-Being in Employees of the Service Industry : A Systematic Evidence Synthesis - Dinesh, Tantri Keerthi; Shetty, Ankitha (Prabandhan: Indian Journal of Management, 2023)
Purpose: The influence of dispositional mindfulness in the service sector employees at the workplace was tremendously accumulating in the context of mental health. Employees in this sector face countless challenges due to workload, target pressure, tight deadlines, and stringent norms that hinder mindful ability at work. A systematic review in this field could be beneficial in identifying the measures, theories, and terminology utilized by researchers to assess the sense of dispositional mindfulness. Methodology: We systematically reviewed quantitative and non-interventional research papers on dispositional mindfulness, which were strongly associated with mental health markers in service sector employees. We proposed to conduct a literature search from 2010 on PubMed, Scopus, and Web of Science databases. This study followed â€œPreferred Reporting Items for Systematic Reviews and Meta-Analysis â€“ Protocolâ€™ (PRISMA-P)â€ guidelines and bibliometric analysis. Findings: This review emerged with themes such as cognitive, emotional, and psychopathological mental health markers, which portrayed the relationship between dispositional mindfulness and the mental health of service sector professionals. Dispositional mindfulness was related to depressive symptoms, anxiety, burnout, stress, and emotional regulation. Practical Implications: This study provided a foundation for researchers, practitioners, and academicians for a better selection of training and therapies related to mindfulness for service sector employees. Future research should be focused on incorporating workplace-based mindfulness interventions for service sector employees to improve their well-being. Originality: Unlike previous research on dispositional mindfulness, the current research attempted to examine the effectiveness of dispositional mindfulness on mental health markers and well-being in service industry employees. Â Systematic Review Registration: PROSPERO 2022 CRD42022296728